Bronchiolitis obliterans organising pneumonia in a patient with ulcerative colitis. - Swinburn, C R (1988)
A young woman with ulcerative colitis developed pneumonia, which responded to corticosteroids. Histological examination showed this to be bronchiolitis obliterans organising pneumonia.